Aggregatibacter Actinomycemcomitans Pneumonia in Children. Issue 1 (January 2015) - Shilo, Smadar; Kassis, Imad; Hakim, Fahed; Shachor-Meyouhas, Yael
<x xml:space="preserve">Abstract</x> Aggregatibacter actinomycemcomitans, previously named Actinobacillus actinomycetemcomitans (Aa), is a facultative Gram-negative slow-growing coccobacillus associated with severe oral and nonoral infections. It is a member of the HACEK group. Pulmonary infection caused by Aa is rare. We describe two cases of Aa pneumonia mimicking malignancy and review published pediatric cases.